Decorative shakahas of the garbhagriha doorframe - Temples of India Project Team (Jio Institute, 2024)
The doorframe of the garbhagriha has multiple shakhas and each shakha is decorated with a specific pattern. The bottom of the shakha depicts river goddesses Ganga, on Makara, and Yamuna on Kachhappa, with their attendants. Above them, beautiful undulating creepers are shown. The shakha next to it shows standing dvarapalas, on each side, holding a weapon and flanked with dwarf figures performing different activities such as dancing, singing, and playing musical instruments.